Critical Role of Molecular Electrostatic Potential on Charge Generation in Organic Solar Cells. Issue 6 (6th April 2018) - Yao, Huifeng; Qian, Deping; Zhang, Hao; Qin, Yunpeng; Xu, Bowei; Cui, Yong; Yu, Runnan; Gao, Feng; Hou, Jianhui
Abstract: Revealing the charge generation is a crucial step to understand the organic photovoltaics. Recent development in non‐fullerene organic solar cells (OSCs) indicates efficient charge separation even with negligible energetic offset between the donor and acceptor materials. These new findings trigger a critical question concerning the charge separation mechanism in OSCs, traditionally believed to result from sufficient energetic offset between the polymer donor and fullerene acceptor. We propose a new mechanism, which involves the molecular electrostatic potential, to explain efficient charge separation in non‐fullerene OSCs. Together with the new mechanism, we demonstrate a record efficiency of ~12% for systems with negligible energetic offset between donor and acceptor materials. Our analysis also rationalizes different requirement of the energetic offset between fullerene‐based and non‐fullerene OSCs, and paves the way for further design of OSC materials with both high photocurrent and high photovoltage at the same time. Abstract : Non‐fullerene acceptors show much larger and uneven ESP distributions than fullerene acceptors, which should play a crucial role in affecting the charge generation in OSCs.